1997
DOI: 10.1021/ma961482v
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of the Imidization of a Poly(ester amic acid) by FT-Raman Spectroscopy

Abstract: The kinetics of thermal imidization of a poly(ester amic acid) in solid state was investigated in the temperature range 120−180 °C. FT-Raman spectroscopy was used for the measurement of imidization. Data on changes in intensity were collected on compressed thin specimens that had been isothermally cured. FT-Raman spectral changes as a function of imidization time are adequately modeled by assuming two first-order imidization reactions. Activation energies for the first and second ring closure processes were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 11 publications
3
22
1
Order By: Relevance
“…Therefore, the reaction rate is strongly dependent on the basicity of the amine, the electrophilicity if the anhydride carbonyl, and the basicity of the solvent. The thermal imidization of poly(amic acid)s involves cyclization through a nucleophilic attack on the acid carbonyl carbon by the free electron pair of the amide nitrogen 34. Although two groups, CONH and COOH, are involved in imidization, this reaction should be treated as first‐order, since these groups belong to the same fragment of poly(amic acid), and interaction of the groups with different macromolecules is practically impossible, especially in the solid state 34.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the reaction rate is strongly dependent on the basicity of the amine, the electrophilicity if the anhydride carbonyl, and the basicity of the solvent. The thermal imidization of poly(amic acid)s involves cyclization through a nucleophilic attack on the acid carbonyl carbon by the free electron pair of the amide nitrogen 34. Although two groups, CONH and COOH, are involved in imidization, this reaction should be treated as first‐order, since these groups belong to the same fragment of poly(amic acid), and interaction of the groups with different macromolecules is practically impossible, especially in the solid state 34.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that E a for thermal imidization of a poly(ester amic acid) is about 20 kJ/mol. 32 In another report, E a for chemical imidization of a poly(amic acid) of 4,4 0 -(hexafluoroisopropylidene)diphthalic anhydride and 1,5-diaminonaphthalene was presented to be 12.3 kJ/mol when an approximately 13:1 molar ratio of amine catalyst to PAA repeating unit was used. 28 …”
Section: Determination Of Activation Energy Of Chemical Imidizationmentioning
confidence: 99%
“…A number of other researchers have noted and studied the reaction kinetics of imide formation [8][9][10][11][12]. There seems to be some agreement that the imidization reaction from the amide-acid proceeds through an initial fast step and a later slower step, although there are differing views on the cause of this difference.…”
Section: Discussionmentioning
confidence: 99%